Anatomical Structure and Fiber Quality of Shorea hopeifolia (Heim) Symington Grown from East Kalimantan - Supartini Supartini; Listya M Dewi; Agus Kholik; M Muslich (Jurnal Ilmu dan Teknologi Kayu Tropis, 2013)
The objectives of this research were focused on description of anatomical structure and fiber quality of Shorea hopeifolia. Wood samples were obtained from Labanan, Berau, East Kalimantan. Anatomical structure and fiber quality of S. hopeifolia were observed according to IAWA List and Indonesian fiber quality criteria. The results showed that S. hopeifolia has brown yellowish heartwood and clearly distinguished with its light yellow sapwood; straight to interlocked grain; somewhat rough texture, slippery touchiness, lustered; and soft to somewhat hard. While the main microscopic are growth rings indistinct; vessel diffuse, simple perforation plate, mostly solitary; alternate and vestured intervessel pit; vessel-ray pits with much reduced borders to apparently simple and rounded shape; tyloses and vacicentric tracheid present; fibres with simple to minutely bordered pits, septate fiber present, thin to thick cell-wall fiber; fiber length 1733 μm; axial parenchyma unilateral paratracheal, vacicentric, aliform, confluent, narrow bands; uniseriate and multiseriate rays (3-8), rays height >1 mm; axial intercellular canal in long tangential lines and radial canal present; prismatic crystals in procumbent and upright rays cells. Based on its fiber dimensions and derived values, S. hopeifolia wood was classified into quality class I and very favourable as raw material for pulp and paper.Key words: anatomical structure, fiber quality, Shorea hopeifolia, yellow meranti